2019
DOI: 10.1101/649996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered protein expression of galactose and N-acetylgalactosamine transferases in schizophrenia superior temporal gyrus

Abstract: Abnormal glycosylation in schizophrenia brain has been previously implicated in disruptions to protein trafficking, localization, and function. Glycosylation is an enzyme-mediated posttranslational modification and, along with reports of altered glycan biosynthesis and abnormal glycan levels in peripheral fluids, growing evidence for altered glycosylation pathway activity in schizophrenia prompted investigation of specific enzymes which may be responsible for these abnormalities. Glycosylation is a highly vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…83 A recent study in schizophrenia postmortem STG found B4GALT1 protein levels reduced, but the patients included in the study were elderly subjects who had primarily been treated with first generation antipsychotics. 72 Together, these reports suggest that both first and second generation antipsychotic medications alter glycosylation pathway activity but may do so via different mechanisms.…”
Section: Evidence Of Altered Glycan Structures In Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…83 A recent study in schizophrenia postmortem STG found B4GALT1 protein levels reduced, but the patients included in the study were elderly subjects who had primarily been treated with first generation antipsychotics. 72 Together, these reports suggest that both first and second generation antipsychotic medications alter glycosylation pathway activity but may do so via different mechanisms.…”
Section: Evidence Of Altered Glycan Structures In Schizophreniamentioning
confidence: 99%
“…Glycosylation enzymes with reported gene and protein expression differences in schizophrenia brain are summarized from refs. [52][53][54][55]70,72 The direction of gene expression differences in schizophrenia for some enzymes were not specified and are indicated with an asterisk (*). Genes which do not demonstrate differential expression in schizophrenia are listed only if both gene and protein expression of the enzyme have been measured.…”
Section: Plasmamentioning
confidence: 99%
See 1 more Smart Citation